2007
DOI: 10.1111/j.1574-6968.2007.00879.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of genes expressed during the developmental stages of the oyster mushroom,Pleurotus ostreatus, using expressed sequence tags

Abstract: In order to isolate and identify the developmentally regulated genes during fruiting body development, cDNA libraries were constructed from eight developmental stages of the Oyster mushroom, Pleurotus ostreatus. From these libraries, 11 761 expressed sequence tags (PoESTs) were generated. Of these, 4060 different genes (PoUnigenes) were identified, representing 34.5% of the entire genome. Redundancy analysis of ESTs during the developmental stages identified eight, 13 and two genes that were specifically expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…PlyA and Pe. ostreolysin (=EryA) (from Pleurotus eryngii), and two aegerolysins from the cocoa tree pathogen, Moniliophthora perniciosa, have all been shown to be present or highly expressed in primordia and fruiting bodies (Berne et al 2002;Fernandez Espinar and Labarere 1997;Joh et al 2007;Kurahashi et al 2014;Lee et al 2002;Vidic et al 2005). Time-course studies performed for the expression of Asphemolysin and terrelysin have also showed that their expression is highest during early fungal growth (Nayak et al 2012;Wartenberg et al 2011).…”
Section: Activities Of the Aegerolysin Proteinsmentioning
confidence: 93%
“…PlyA and Pe. ostreolysin (=EryA) (from Pleurotus eryngii), and two aegerolysins from the cocoa tree pathogen, Moniliophthora perniciosa, have all been shown to be present or highly expressed in primordia and fruiting bodies (Berne et al 2002;Fernandez Espinar and Labarere 1997;Joh et al 2007;Kurahashi et al 2014;Lee et al 2002;Vidic et al 2005). Time-course studies performed for the expression of Asphemolysin and terrelysin have also showed that their expression is highest during early fungal growth (Nayak et al 2012;Wartenberg et al 2011).…”
Section: Activities Of the Aegerolysin Proteinsmentioning
confidence: 93%
“…Recent work has brought more understanding of these functions and new methods have been introduced for more systematic studies. In one study, expressed sequence tags were used to study gene expression during different developmental stages in the edible oyster mushroom, Pleurotus ostreatus [66]. In Beauveria bassiana, hydrophobins were pointed out to have key roles in adhesion and for cell surface properties [67].…”
Section: Biological Function Of Hydrophobinsmentioning
confidence: 99%
“…Exploratory multivariate statistical models can be used to identify differences in gene expression patterns between treatments, and along environmental gradients. Examples include: Between Group Analysis (Culhane et al, 2002), Redundancy Analysis (RDA; Joh et al, 2007), Canonical Correspondence Analysis (CCA; Liang et al, 2010), Permutational Multivariate Analysis of Variance (PERMANOVA; Anderson, 2001;Zapala and Schork, 2006), or Analysis of Similarities (ANOSIM; Huse et al, 2010). The advantage of RDA, CCA and BGA is that they allow the relationships between sites, species and treatments to be interpreted concomitantly.…”
Section: Statistical Analysesmentioning
confidence: 98%